Influence of pre drying treatment on physical properties of carrots - Barroca, Maria João (2014)
In the present work, the effect of pre-treatment of ascorbic acid on color changes and texture was investigated during convective hot air drying at 60ºC. The pre-treatments were done at 0.25 % and 1 % of ascorbic acid with treatment times of 60 and 90 minutes. Changes in color and total color difference were evaluated by the CIELab color system and texture of dried carrots was accessed in terms of hardness, springiness, and cohesiveness. Regarding the total color difference, soaking carrots in ascorbic acid at both concentrations and treatment times turned out to be an ineffective method for reducing the browning reactions during drying. With respect to textural attributes non-significant differences were observed in springiness and cohesiveness of untreated and pre-treated dried carrots but the hardness increased at a pre-treatment time of 90 minutes.